Trends of Teenage Pregnancy and Pregnancy Outcomes - Tippawan Liabsuetrakul (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Adolescent birth rate is one of expanded indicators of Millennium Development Goal5 in addition to the maternal mortality ratio, delivery by skilled birth attendant, contraceptive prevalence rate and antenatal care coverage(1). Adolescent or teen is defined as women when aged 10-19 years by WHO definition which called as adolescents aged 15-19 years and younger adolescent when aged 10-14 years(2,3). Adolescent birth rate is calculated as the number of teens giving birth per 1000 adolescent population(1)